Fabrication and spectral properties of Dy:Y2O3 transparent ceramics - Hu, Zongwen (2020)
Dy3+-doped Y2O3 ceramics were fabricated by Spark Plasma Sintering method. The effect of sintering temperature on the microstructure and the optical transmittance of the ceramics was studied. The maximum in-line transmittance of Dy:Y2O3 ceramics with thickness of 1 mm was 74.5% at 574 nm when sintering temperature was 1550 ℃. The spectroscopic parameters were determined by Judd-Ofelt theory based on the room temperature absorption spectra. The peak emission cross section for the 4F9/2 → 6H13/2 transition was calculated to be 0.569 × 10−20 cm2. The fluorescence decay curve and quantum efficiency of the 4F9/2 multiplet were measured to be 269.2 μs and 37.1%, respectively.